2019
DOI: 10.1101/606731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CD4 T-cell transcriptome expression reversal of the lncRNA-mRNA co-expression network in elite controllervs.normal-process HIV patients

Abstract: 21 22 42 will help researchers and clinicians to understand the interrelationship between HIV 43 and the host. In the present study, we focused on the interactions and functional 44 relationships between significantly differentially expressed long non-coding RNAs 3 45 (lncRNAs) and mRNAs in ECs vs. normal-process patients (NPs). RNA-sequencing 46 was performed for six representative samples of CD4 T-cells. Using the Pearson 47 correlation test, an lncRNA-mRNA co-expression network was constructed. Several 48 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Additionally, one could perform RNA-seq analyses at the different phases of HIV-1 infection in target human T cells that would aid in identifying unique signatures. For example, Chen et al (2019) determined the lncRNA-mRNA co-expression profiles in elite controllers versus normal-process HIV-1 patients [22], and found that these profiles were differentially enriched in immune response-regulating signaling and apoptosis pathways [22]. Alternatively, one could screen based on lncRNA mechanism.…”
Section: Lncrnas As Therapeutic Targets For Hiv-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, one could perform RNA-seq analyses at the different phases of HIV-1 infection in target human T cells that would aid in identifying unique signatures. For example, Chen et al (2019) determined the lncRNA-mRNA co-expression profiles in elite controllers versus normal-process HIV-1 patients [22], and found that these profiles were differentially enriched in immune response-regulating signaling and apoptosis pathways [22]. Alternatively, one could screen based on lncRNA mechanism.…”
Section: Lncrnas As Therapeutic Targets For Hiv-1mentioning
confidence: 99%
“…This subpopulation of CD4+ T cells remain a challenge to current treatment strategies that are only able to effectively target actively replicating cells [20]. Over the past decade, the role of lncRNAs in modulating HIV-1 has broadened our understanding of how host factors can maintain viral latency and facilitate HIV-1 replication in target host cells [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%